2021
DOI: 10.1021/acs.jced.1c00453
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria on the Reciprocal Quaternary System K+, Rb+ // Cl, and Borate–H2O at T = 323.2 K and p = 94.77 kPa

Abstract: The isothermal dissolution method was applied for the phase equilibrium experiment of the quaternary system K+, Rb+ // Cl–, and borate–H2O at T = 323.2 K and p = 94.77 kPa. The solubilities and refractive indices (n D) of the system were determined experimentally. The coexisting salts of the quaternary invariant points were identified using the X-ray diffraction (XRD) method. Based on the measured data, the stable phase diagram and the figures of water content and refractive index (n D) vs composition were plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In Figure , points A–E represent the invariant points of ternary subsystems NH 4 + , Ca 2+ //Cl – –H 2 O, Mg 2+ , Ca 2+ //Cl – –H 2 O, NH 4 + , Mg 2+ //Cl – –H 2 O, respectively, and points F 1 to F 3 represent the invariant points of quaternary system NH 4 + , Mg 2+ , Ca 2+ //Cl – –H 2 O. According to the method of judging the type of invariant points described in the literature, we can judge that points F 1 to F 3 are all commensurate type saturation points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure , points A–E represent the invariant points of ternary subsystems NH 4 + , Ca 2+ //Cl – –H 2 O, Mg 2+ , Ca 2+ //Cl – –H 2 O, NH 4 + , Mg 2+ //Cl – –H 2 O, respectively, and points F 1 to F 3 represent the invariant points of quaternary system NH 4 + , Mg 2+ , Ca 2+ //Cl – –H 2 O. According to the method of judging the type of invariant points described in the literature, we can judge that points F 1 to F 3 are all commensurate type saturation points.…”
Section: Resultsmentioning
confidence: 99%
“…, respectively, and points F 1 to F 3 represent the invariant points of quaternary system NH 4 + , Mg 2+ , Ca 2+ //Cl − −H 2 O. According to the method of judging the type of invariant points described in the literature, 26 we can judge that points F 1 to F 3 are all commensurate type saturation points.…”
Section: Methodsmentioning
confidence: 99%
“…In the previous research about the chloride type system containing potassium and rubidium at 323.2 K, ,, the solid solution [(K, Rb)­Cl] was formed in the system. However, when the anions are chloride and boron, and the coexisting cations are still potassium and rubidium, the crystals of solid solution are only found in the form of [(K, Rb)­Cl].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, a series of phase equilibria studies have been done aimed at different types of brine. As for the main components of the Pingluo brine, they can be simplified as the Li + , Na + , K + , Rb + , Mg 2+ //Cl – , Borate-H 2 O system. Therefore, to understand the thermodynamic behaviors of the complex system, phase diagrams of some subsystems have been measured. For the borate-containing system, the crystalline form of boron appears in many polymeric forms such as BO 2 – , B­(OH) 4 – , B­(OH) 3 , B 4 O 7 2– , and B 5 O 8 – when the coexisting ions and temperature change. , As for the quinary system Li + , K + , Rb + //Cl – , Borate-H 2 O at 323.2 K, the corresponding nine ternary subsystems and five quaternary subsystems at 323.2 K have been studied. The research results show that two boron species, B 4 O 7 2– and B 5 O 8 – , were found in the borate system containing potassium/lithium and rubidium; the solid solution [(K, Rb)­Cl] was formed in the chloride type system containing potassium and rubidium; and the rubidium carnallite RbCl·MgCl 2 ·6H 2 O was found in the chloride type system containing magnesium and rubidium. Commonly, the coexisting ions in the solution have a direct effect on the crystallization form of salts.…”
Section: Introductionmentioning
confidence: 99%
“…−H 2 O, 10 Li + , Mg 2+ //Cl − − H 2 O, 11,12 Li + , K + //Cl − −H 2 O, 12 K + , Rb + //Cl − −H 2 O, 13 and K + , Mg 2+ //Cl − −H 2 O; 13 quaternary systems Li + , K + , Rb + // borate−H 2 O, 14 K + , Rb + //Cl − , borate−H 2 O, 15 Li + , Rb + //Cl − , borate−H 2 O, 16 and Li + , Mg 2+ //Cl − , borate−H 2 O; 17 quinary systems Li + , K + , Rb + , Mg 2+ //borate−H 2 O, 18, 19 Li + , K + , Rb + , Mg 2+ //Cl − −H 2 O, 20 Li + , K + , Rb + //Cl − , borate−H 2 O, 21 and Li + , Na + , Mg 2+ //Cl − , B 4 O 7 2− −H 2 O. 22 The results of studies show that lithium carnallite LiCl•MgCl 2 •7H 2 O is easily produced in the chloride coexistence system of lithium and magnesium, carnallite KCl•MgCl 2 •6H 2 O is formed in the coexistence system of potassium and magnesium, rubidium carnallite RbCl•MgCl 2 •6H 2 O is found in the chloride type system containing magnesium and rubidium, and solid solution [(K, Rb)Cl] is formed in the coexistence system of potassium and rubidium.…”
Section: Introductionmentioning
confidence: 99%